594 A Neonatal Rat Model of Bronchopulmonary Dysplasia Induced by Pre- And Postnatal Inflammation without Exposure to Hyperoxia. (October 2012) - Choi, CW; Lee, HJ; Lee, YJ; Lee, JM; Lee, JA; Kim, EK; Kim, HS; Kim, BI; Choi, JH
Abstract : Purpose: We tested if pre- or postnatal inflammation can develop BPD per se and if there are any interaction between prenatal and postnatal inflammation. Methods: Two days before delivery (E20), 1 µg of lipopolysaccharide (LPS) or vehicle (V) was injected into each amniotic sac, and after birth 0.25 mg/kg of LPS or vehicle was injected into peritoneum on P1, P3, and P5. This led to four experimental groups. On P7 and P14, their lungs and hearts were harvested, and alveolarization and lung vascular density were evaluated. Results: Morphometric analysis of P7 lungs revealed that both preLPS+postLPS group and V+postLPS group had significantly larger and less complex airspaces and small alveolar surface area than V+V group. On P14, only V+postLPS group had significantly larger and less complex airspaces than V+V group. Howevere, alveolar surface areas were significantly smaller both in preLPS+postLPS group and V+postLPS group than in V+V group. Lung vascular density of both preLPS+postLPS group and V+postLPS group was significantly lesser than V+V group. Conclusions: At these intra-amniotic and postnatal systemic LPS doses, prenatal intra-amniotic LPS injection per se did not affect postnatal alveolar and pulmonary vascular development, while postnatal systemic LPS injection significantly inhibited alveolar and pulmonary vascular development regardless of whether prenatal intra-amniotic LPS was injected or not. There was no definite interaction between intra-amniotic LPS and postnatal systemic LPS on the lung development. This rat model of BPD could be used as a valuable tool for testing the effect of anti-inflammatory agents on the prevention of BPD.